1999
DOI: 10.1007/bf02467607
|View full text |Cite
|
Sign up to set email alerts
|

Normal-phase high performance liquid chromatographic separation and characterization of short- and long-chain triacylglycerols

Abstract: Short-and long-chain triacylglycerols (SLCT) are a family of lipids prepared by chemical or enzymatic interesterification of triacetin, tripropionin and/or tributyrin, and long-chain (C16!18) hydrogenated vegetable oils. In this study, a normal-phase cyanopropyl high-performance liquid chromatographic (HPLC) method was developed for the separation and quantification of SLCT. The method is capable of separating SLCT mixtures, free fatty acids and the neutral lipid classes of saturated long-chain triacylglycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…The ratio of the two SL types in the final product was dependent on the molar ratio of reactants used. From previous studies on the interesterification of triacetin with HSO, a ratio of 2:1 was optimal [7] and this was the ratio used in this work. HPLC analysis of the MLCT product produced by acidolysis of tributyrin with stearic acid under the reaction conditions used in this study gave the chromatograms shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the two SL types in the final product was dependent on the molar ratio of reactants used. From previous studies on the interesterification of triacetin with HSO, a ratio of 2:1 was optimal [7] and this was the ratio used in this work. HPLC analysis of the MLCT product produced by acidolysis of tributyrin with stearic acid under the reaction conditions used in this study gave the chromatograms shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The NPcN-HPLC gradient used was reported previously [6]. For the NPslL-HPLC method, an isocratic binary mobile phase consisting of 15% MTBE and 85% hexane (v/v, each fortified with 0.4% acetic acid) was used at a flow rate of 0.75mLmin 1 [7]. The ELSD detector was operated at 40 ~ with nitrogen nebulizing gas flow of 1.51 SLPM for both NP methods.…”
Section: Analysis Of Productsmentioning
confidence: 99%
“…In the last few years, PVA columns [11,12], diol columns [13,14], and amino columns [15,16] have been used by other groups in the separation of polar lipid classes. Cyanopropyl columns have been employed in the separation of non-polar lipid classes, mainly in applications related to transesterification reaction products [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of this approach is limited in complex mixtures with abundant interferences, and it does not provide information about the identity of individual TAG species. Several chromatographic methods were implemented for the separation of TAG ( 27 ), among which the three mainstream approaches are normal phase liquid chromatography (NP-LC) (28)(29)(30), silver-ion liquid chromatography (Ag-LC) ( 4,5,27,(31)(32)(33)(34), and nonaqueous reversed phase liquid chromatography (NARP-LC) ( 5,13,19,(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%